Conceptual support for the formation of an information environment for stakeholder interaction in the preparation phase of infrastructure projects - Malykhin , M. (Ways to Improve Construction Efficiency, 2024)
In the modern context of implementing large-scale infrastructure projects, the effective organization of interaction among all construction process stakeholders gains critical importance. The increasing volume of data, the digitalization of management processes, and growing demands for decision coherence necessitate the creation of an integrated information environment that ensures operational, transparent, and adaptive communication between all stakeholders. In this context, the need arises for a conceptual foundation for constructing such environments that can unify digital models, coordination tools, data exchange algorithms, and procedures for verifying managerial actions at the project preparation stage. This work emphasizes the necessity of transitioning from fragmented coordination to a systemic information-driven governance model, in which each participant has access to real-time updated data, and every decision is logged with traceability regarding its impact on other system components. Particular attention is devoted to the issues of inter-institutional integration of information systems, standardization of digital interaction formats, and the formalization of data verification procedures circulating within the system. The article highlights the role of digital control dashboards, automated conflict detection systems, scenario risk forecasting tools, and digital decision-approval protocols. A specific focus is given to the linkage between the information environment and tender planning procedures, assessment of technical solutions, scheduling, and supply chain systems. The study explores real-world examples of digital tool implementation for coordination among municipal authorities, developers, and financial institutions during the execution of urban infrastructure projects. The rationale for developing digital ecosystems based on open architecture and modular logic, enabling function expansion according to project phases, is substantiated.